Epigenomic signatures associated with spontaneous and replication stress-induced DNA double strand breaks - Kodali, Sravan; Meyer-Nava, Silvia; Landry, Stephen; Chakraborty, Arijita; Rivera-Mulia, Juan Carlos; Feng, Wenyi (Frontiers in Genetics, 2022)
Common fragile sites (CFSs) are specific regions of all individuals’ genome that are predisposed to DNA double strand breaks (DSBs) and undergo subsequent rearrangements. CFS formation can be induced in vitro by mild level of DNA replication stress, such as DNA polymerase inhibition or nucleotide pool disturbance. The mechanisms of CFS formation have been linked to DNA replication timing control, transcription activities, as well as chromatin organization. However, it is unclear what specific cis- or trans-factors regulate the interplay between replication and transcription that determine CFS formation. We recently reported genome-wide mapping of DNA DSBs under replication stress induced by aphidicolin in human lymphoblastoids for the first time. Here, we systematically compared these DSBs with regards to nearby epigenomic features mapped in the same cell line from published studies. We demonstrate that aphidicolin-induced DSBs are strongly correlated with histone 3 lysine 36 trimethylation, a marker for active transcription. We further demonstrate that this DSB signature is a composite effect by the dual treatment of aphidicolin and its solvent, dimethylsulfoxide, the latter of which potently induces transcription on its own. We also present complementing evidence for the association between DSBs and 3D chromosome architectural domains with high density gene cluster and active transcription. Additionally, we show that while DSBs were detected at all but one of the fourteen finely mapped CFSs, they were not enriched in the CFS core sequences and rather demarcated the CFS core region. Related to this point, DSB density was not higher in large genes of greater than 300 kb, contrary to reported enrichment of CFS sites at these large genes. Finally, replication timing analyses demonstrate that the CFS core region contain initiation events, suggesting that altered replication dynamics are responsible for CFS formation in relatively higher level of replication stress.